Assessing the Technological Competencies of Library and Information Science Graduates and Their Employment Outcomes: A Case Study of Pakistan. Issue 5 (4th July 2021) - Tahir, Muhammad; Warraich, Nosheen Fatima
Abstract: The purpose of this study was to compare the self-perception of early career Library and Information Science (LIS) graduates' Information and Communications Technology (ICT) competencies with the expectations of senior Library and Information Science (LIS) professionals' in Pakistan. A quantitative research approach based on a survey was used in the study. Purposive sampling technique was employed to collect data from 100 early career LIS graduates and 100 LIS professionals having more than five years' experience through a questionnaire. The researcher received 89 questionnaires from senior LIS professionals and 91 from early-career Department of Information Management (DoIM) graduates resulting in a 89% and 91% response rate respectively. The results of the study indicate that there is a gap between the expectations of senior LIS professionals' and the perceptions of early career LIS graduates' regarding their ICT competencies. Senior LIS professionals expected that early-career LIS graduates would have a working knowledge of Microsoft Office, computer operating systems, computer hardware and functions, social networking sites, electronic database searching, and institutional repository software. Senior LIS professionals also expected that early career LIS graduates should be familiar with research management tools such as Endnote, Mendeley and Zotero, integrated library systems and plagiarism detection software such as Turnitin and SafeAssign. The early career LIS graduates reported that they were expected to have knowledge of above-said expertise and that iy was considered essential for their future jobs. The findings of the study would be beneficial for the faculty of library schools and policymakers to make changes in the curriculum so as to minimize the gap between academia and the industry.